Two-Dimensional Packing for Irregularly Shaped Objects - CHEN, Ping (Institutional Knowledge at Singapore Management University, 2003)
Packing problems arise in a wide variety of application areas. The basic problem is that of determining an efficient arrangement of different objects in a region without any overlap. The simplest packing problem is rectangular packing, where both the objects and the region are rectangular. Many research works have been done on two and three dimensional rectangular packing. However there are many situations when either objects or the containing region is irregular in shape. In the project, we concentrate on two-dimensional packing problems involving irregular shaped objects (both convex and concave). We have applied several approaches to solve such problems.